The Effect of Servicescape in Hotels on Customer Satisfaction: Evidence From Resort Hotels - ARTUĞER, Savaş (Turizam, 2020)
The purpose of this study was to determine the impact of servicescapes in hotels on customer satisfaction. The sample of the study consists of foreign tourists staying in five-star resort hotels operating in Marmaris district of Muğla province between June 1-August 30, 2019. Data were collected from 225 hotel customers. Mean, standard deviation, confirmatory factor analysis, reliability analysis and regression analysis were used in analyzing the obtained data.The study revealed that servicescape in hotels has an impact on customer satisfaction. It was found that ambient conditions, decor, signs and symbols had a significant effect on customer satisfaction. According to the results of the study, signs and symbols are the most important factors affecting customer satisfaction. However, it was discovered that the spatial layout did not affect customer satisfaction.
Keywords: servicescape; customer satisfaction; resort hotels